2019
DOI: 10.1038/s41467-019-11987-z
|View full text |Cite
|
Sign up to set email alerts
|

Tropane alkaloids biosynthesis involves an unusual type III polyketide synthase and non-enzymatic condensation

Abstract: The skeleton of tropane alkaloids is derived from ornithine-derived N -methylpyrrolinium and two malonyl-CoA units. The enzymatic mechanism that connects N -methylpyrrolinium and malonyl-CoA units remains unknown. Here, we report the characterization of three pyrrolidine ketide synthases (PYKS), Aa PYKS, Ds PYKS, and Ab PYKS, from three different hyoscyamine- and scopolamine-producing plants. By e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…Recently, the enzymes that are required to form the characteristic seven-membered tropane ring have been described. [152][153][154] Pyrrolidine ketide synthase (PYKS), a type III polyketide synthase, catalyses the formation of 3-oxoglutaric acid from two malonyl-CoA units. PYKS has an active site with the typical type-III PKS catalytic triad for substrate loading and chain extension (Cys166, His305 and Asn338), but has additional residues (Arg-134 and Ser-340) which limit the enzyme to a single extension step by interacting with the substrate carboxylate moiety.…”
Section: Polyamine-derivedmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the enzymes that are required to form the characteristic seven-membered tropane ring have been described. [152][153][154] Pyrrolidine ketide synthase (PYKS), a type III polyketide synthase, catalyses the formation of 3-oxoglutaric acid from two malonyl-CoA units. PYKS has an active site with the typical type-III PKS catalytic triad for substrate loading and chain extension (Cys166, His305 and Asn338), but has additional residues (Arg-134 and Ser-340) which limit the enzyme to a single extension step by interacting with the substrate carboxylate moiety.…”
Section: Polyamine-derivedmentioning
confidence: 99%
“…PYKS has an active site with the typical type-III PKS catalytic triad for substrate loading and chain extension (Cys166, His305 and Asn338), but has additional residues (Arg-134 and Ser-340) which limit the enzyme to a single extension step by interacting with the substrate carboxylate moiety. 153 When incubated with PYKS, N-methylpyrollinium and malonyl-CoA form 4-(1-methyl-2-pyrrolidinyl)-3-oxobutanoic acid, a key intermediate. 152,153 PYKS forms 3-oxoglutaric acid from malonyl-CoA and releases it into the solvent where it spontaneously reacts with N-methylpyrollinium through a decarboxylative Mannich condensation.…”
Section: Polyamine-derivedmentioning
confidence: 99%
See 2 more Smart Citations
“…The 4-arylaminopiperidine is a structural moiety found in many alkaloids [4][5][6][7][8][9][10][11] and pharmaceutical products such as fentanyl and structurally-related analgesic opioids or H1-antihistamines agents such as bamipine [12][13][14][15][16][17] and neurokinin 1 (NK1) receptor antagonists [18][19][20]. Studies have shown that compounds with piperidine rings [4,8,[21][22][23][24][25][26] have good selectivity and activity for the P. falciparum strain.…”
Section: Introductionmentioning
confidence: 99%